A Framework for Enhancing Multicultural Counselling Competence - Collins, Sandra; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2008)
Canadian counsellors are increasingly called upon to work with diverse client populations whose needs may not be met through traditional counselling models. The question for many is how to development the attitudes, knowledge, and skills for competent and ethical practice. This article introduces core competencies designed to assist counsellors to effectively infuse culture into all aspects of the counselling process. It then describes how these competencies are combined to enhance the multicultural competence of counsellors. Practical strategies are then introduced to provide a starting place for counsellors who identify the need for further professional development to increase their multicultural competence.